Novel desferrioxamine derivatives synthesized using the secondary metabolism-specific nitrous acid biosynthetic pathway in Streptomyces davawensis. (November 2018) - Hagihara, Ryota; Katsuyama, Yohei; Sugai, Yoshinori; Onaka, Hiroyasu; Ohnishi, Yasuo
Abstract Recently, a novel nitrous acid biosynthetic pathway composed of two enzymes was discovered to be involved in the biosynthesis of cremeomycin for the formation of its diazo group. In this pathway, CreE oxidizesl -aspartic acid to nitrosuccinic acid and CreD liberates nitrous acid from nitrosuccinic acid. Bioinformatic analysis showed that various actinobacteria have putative secondary metabolite biosynthesis gene clusters containingcreE andcreD homologs, suggesting that this pathway is widely used for the biosynthesis of various natural products. Here, we focused oncreE andcreD homologs (BN159_4422 andBN159_4421 ) inStreptomyces davawensis . In vitro analysis of recombinant BN159_4422 and BN159_4421 proteins showed that these enzymes synthesized nitrous acid froml -aspartic acid. Secondary metabolites produced by this gene cluster were investigated by comparing the metabolic profiles of the wild-type and ΔBN159_4422 strains. When these strains were co-cultured withTsukamurella pulmonis TP-B0596, three compounds were specifically produced by the wild-type strain. These compounds were identified as novel desferrioxamine derivatives containing either of two unique five-membered heterocyclic ring structures and shown to have iron-binding properties. A putative desferrioxamine biosynthetic gene cluster was found in theS. davawensis genome, and inactivation of adesD homolog (BN159_5485 ) also abolished the production of these compounds. We propose that these compounds should be synthesized by the modification of desferrioxamine B and a shorter chain analog using nitrous acid produced by the CreE and CreD homologs. This study provides an important insight into the diverse usage of the secondary metabolism-specific nitrous acid biosynthetic pathway in actinomycetes.